Pengaruh Gerak dan Lagu terhadap Kecerdasan Kinestetik Anak Usia 5-6 Tahun di TK Chairul Athfal Belawan - Syarifa Destriadinda (Medan Resource Center, 2021)
The formulation of the problem in this study is whether there is an influence of motion and song on the kinesthetic intelligence of children aged 5-6 years in Chairul Athfal Belawan Kindergarten?. The research design used in this study is a one-group pretest-posttest. The population in this study were all children of group B in TK Chairul Athfal Belawan. The sampling technique used is saturated sampling where all members of the population are used as samples. The sample of this study were all children in group B in TK Chairul Athfal Belawan, totaling 15 children consisting of 8 boys and 7 girls. Data collection techniques obtained by observation and documentation. The data analysis technique used in analyzing the research data is normality test and hypothesis testing. Based on the results of the pre-test study, the average pre-test value was 9.8 and the post-test results obtained an average value of 11.9. Based on the results of the t-test calculation, it is obtained that tcount > ttable (6.49 > 2.144) with a significance value of 0.000 less than 0.05, it can be stated that Ha is rejected and Ho is accepted, which means that there is an influence of motion and song on the kinesthetic intelligence of children aged 5-6 years in TK Chairul Athfal Belawan Academic Year 2020/2021.